Budaya Bertoilet: Duduk atau Jongkok? (ETNOSIA : Jurnal Etnografi Indonesia, 2016)
AbstractPublic toilet is one of the important parts of the building that many aspects of design have to be  taken into account to build. Many public  toilets are built just by looking at the outer performance without considering whether or not the target user will fit with the design. This article deals with this. It examines how toilet is perceived by the users, what type of toilet is preferred and why, and how they utilize public toilet. The interaction between western and eastern culture in the toiletdesign has resulted in cultural shock and stuttering technology among the toilet users in regard to the use of toilet because the influx of western culture is not balance with the introduction of the new culture. Whether one chooses squatting or sitting toilet, it is not only related to universal issues about modernity, luxury, cleanliness, and health. Toilet is not solely function as a disposal waste container, but it is also a place for one to seclude him/herself from others, to relax and to create new ideas. Toilet is a symbol to show ones’ identity. But how one use the toilet is closely associated with one’s perception about toilet, gender, health, cleanliness, Islamic ethics, and body proportion. Key words: toilet, sitting toilet, squatting toilet, modernity.